2005
DOI: 10.1108/14777260510600022
|View full text |Cite
|
Sign up to set email alerts
|

Ways to reduce patient turnaround time and improve service quality in emergency departments

Abstract: The study covers several hospitals and analyses over 20,000 process components; as such the common findings may serve as guidelines to other hospitals when addressing this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…This conclusion does support previous findings that staffs' perceptions do depend on their role and interaction with their patients, with nurses having more interaction with patients during this time period [12] . This study found, as did Sinreich, et al, that the nurses versus doctors and patients were correct in stating the real reasons for delay [9] . This however was only for a specific time period with what were more complicated cases.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This conclusion does support previous findings that staffs' perceptions do depend on their role and interaction with their patients, with nurses having more interaction with patients during this time period [12] . This study found, as did Sinreich, et al, that the nurses versus doctors and patients were correct in stating the real reasons for delay [9] . This however was only for a specific time period with what were more complicated cases.…”
Section: Discussionsupporting
confidence: 58%
“…The secondary explanation is due to internal factors such as delays in radiology, laboratory and availability of beds [4][5][6][7][8] . Sinreich, et al, in a comprehensive study of major hospitals, found the chief culprit of long wait times was delayed access to auxiliary services [9] . They found that 51 to 63 percent of the total patient turnaround time was due to time waiting for x-ray examinations, the first physician's examination and waiting time for blood.…”
mentioning
confidence: 99%
“…Certain studies suggest that the TAT of laboratory tests directly influences the duration of stay of patients in the Emergency Department (ED) [5], as a reduction of laboratory TAT reduces ED stay [6], and hence enhances the safety and satisfaction of patients [7]. Decreasing the TAT of laboratory tests, help in reducing overcrowding in the ED [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way in [21] the resizing of different resources is compared in order to identify which is the one that mainly influences ED performances. Patients arrival pattern can be also simulated in order to level the peak of resource utilization, leading to a significantly better planning of staff and resources [29]. Similarly, in [30] arrival analysis allows a reduction of patient turnaround times.…”
Section: Literature Reviewmentioning
confidence: 99%